How to create a healthy lifestyle (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
their comprehensive guide to a healthy lifestyle discusses how to be mentally healthy, how to exercise, how to eat healthy and how to lose weight.